A proposed model of Width-Thickness Ratio for tidal shelf sand ridge reservoirs within Upper Cibulakan Fm. in the Ajata Field, Offshore Northwest Java Basin - Dani Setiawan, Priantoro Kartika; Amrizal, Amrizal; Setiawati, Yasinta Dewi; Mansur, Achmad (Berita Sedimentologi, 2024)
The Upper Cibulakan reservoir of the Ajata Field in the Northwest Java Basin represents tidal shelf sand ridges deposited in an open-mouthed shallow marine environment. One hundred fifty-three wells have been drilled to develop this reservoir since 1970. The average density of wells in the Ajata Field is 400-500 m, making it an ideal case for reconstructing tidal shelf sand ridges reservoir model. This study aims to determine tidal shelf sand ridges heterogeneity and geometry, especially through width-thickness ratio, in the Ajata Field and to identify similar reservoirs in other fields or basins. The data used in this study are 900 ft conventional core data, 74 Routine Core Analysis (RCA) data, 152 well logs, and 3D seismic data.Tidal shelf sand ridges conventional cores analysis shows six lithofacies in the Upper Cibulakan Formation, namely: claystone-siltstone, lenticular siltstone, flaser sandstones, cross-bedded sandstones, non-calcareous massive sandstones, and calcareous sandstones. These six lithofacies are grouped into four facies associations and they reflect the tidal shelf ridge development stages: embryonic, immature accretion, mature accretion, and abandonment. These facies associations create a cyclicity pattern bounded by chronostratigraphic markers of marine flooding surfaces. Well-to-well correlation and seismic interpretation results show several trends and geometry of the tidal shelf sand ridges. Three zones of width thickness ratio (W-T) analysis in every parasequence are concluded in this study: Zone I (width: maximum 800 m; thickness: less than 25 ft), Zone II (width: 700 – 1300 m; thickness: 25 – 45 ft), and Zone III (width: 1000 – 1900 m; thickness: thicker than 45 ft).